Parenting as a Warning Tool of Juvenile Delinquency - BAIMAKHANOV, Artur A.; KURSABAEVA, Zarina I.; AMURTAEVA, Dinara T.; NARBINOVA, Mirgul M.; BEGALIУEV, Yernar N. (Journal of Advanced Research in Law and Economics; Vol 9 No 7 (2018): JARLE Volume IX Issue 7(37) Winter 2018DO - 10.14505//jarle.v9.7(37).06, 2019)
The relevance of the article lies in the fact that minors represent one of the most vulnerable segments of the population, and only knowledge of the moral and psychological characteristics of adolescents, their comprehensive and integrated accounting by all bodies, organizations, institutions, individuals, one way or another working with minors, can improve education of such persons. Also, the neglect of parenting is one of the main causes of juvenile delinquency. The purpose of the article is to analyze education as a tool in the prevention of juvenile delinquency. The article analyzes the problems of preventing juvenile delinquency. A brief outline describes the characteristics of education, family, and family well-being. The authors believe that the main reason for the increase in crime among children is associated with a low level of compliance with the requirements for parenting with regard to them, the lack of a proper approach to this problem, both from the public and from the authorized bodies. Thus, the exclusive role of ‘education’ as the main tool in the prevention of juvenile delinquency, as well as some aspects of the improper performance of responsibilities for raising a minor, are noted.